Hexon-only binding of VP26 reflects differences between the hexon and penton conformations of VP5, the major capsid protein of herpes simplex virus. - Wingfield, P T (1997)
VP26 is a 12-kDa capsid protein of herpes simplex virus 1. Although VP26 is dispensable for assembly, the native capsid (a T=16 icosahedron) contains 900 copies: six on each of the 150 hexons of VP5 (149 kDa) but none on the 12 VP5 pentons at its vertices. We have investigated this interaction by expressing VP26 in Escherichia coli and studying the properties of the purified protein in solution and its binding to capsids. Circular dichroism spectroscopy reveals that the conformation of purified VP26 consists mainly of beta-sheets (approximately 80%), with a small alpha-helical component (approximately 15%). Its state of association was determined by analytical ultracentrifugation to be a reversible monomer-dimer equilibrium, with a dissociation constant of approximately 2 x 10(-5) M. Bacterially expressed VP26 binds to capsids in the normal amount, as determined by quantitative sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Cryoelectron microscopy shows that the protein occupies its usual sites on hexons but does not bind to pentons, even when available in 100-fold molar excess. Quasi-equivalence requires that penton VP5 must differ in conformation from hexon VP5: our data show that in mature capsids, this difference is sufficiently pronounced to abrogate its ability to bind VP26.